PEMBENTUKAN KARAKTER KEJUJURAN KELAS V SDN 52 GEDONG TATAAN OLEH GURU PENDIDIKAN AGAMA ISLAM - Rindi Onky Saputri; Mashdaria Huwaina; Anggi Septia Nugroho (Ta'lim, 2023)
ABSTRACTThe character of honesty, namely how the role of an Islamic Religious Education teacher is in forming the character of honesty in students, so that students at SDN 52 Gedong Tataan are formed there is an honesty in these students. For a teacher to direct and foster students to be able to grow and develop. Of the many problems that occur in the world of education, namely dishonesty committed by students, namely lying, making up blind words, cheating, and not admitting mistakes,This study uses a qualitative approach, with data collection techniques such as observation, interviews, and documentation in inductive qualitative research. In this research, the objects are school principals, Islamic religious education teachers, and students.The results of the study showed that dishonesty at SDN 52 Gedong Tataan, Pesawaran Regency, Lampung Province, namely telling lies, not admitting mistakes, making up things and cheating. In preventing student dishonesty, the role of the PAI teacher in shaping the character of honesty in grade V students at SDN 52 Gedong Tataan, Pesawaran Regency, is as follows: giving advice, setting an example, being given punishment and reward.It can be concluded that the role of the Islamic Religious Education teacher in shaping the character of the honesty of fifth grade students at SDN 52 Gedong Tataan is to provide advice, lead by example, punish, and reward. In forming the honest character of students, the role of the PAI teacher must work together with several parties, including the principal, homeroom teacher, student guardians and the surrounding environment or community from adults to peers.